2010
DOI: 10.1099/mic.0.030270-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting interactions between nucleosides and germination receptors in Bacillus cereus 569 spores

Abstract: Bacillus cereus 569 spores germinate either with inosine as a sole germinant or with a combination of nucleosides and L-alanine. Whereas the inosine-only germination pathway requires the presence of two different germination receptors (GerI and GerQ) to be activated, the nucleoside/alanine germination pathway only needs one of the two receptors. To differentiate how nucleoside recognition varies between the inosine-only germination pathway and the nucleoside/ alanine germination pathway, we tested 61 purine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…For taurocholate titrations, spores were exposed to various concentrations of taurocholate (8,10,14,20, and 30 mM) at specific constant glycine concentrations (8, 9, 10, 13, and 16 mM). For glycine titrations, spores were exposed to various concentrations of glycine (8,10,12,14, and 18 mM) at specific constant taurocholate concentrations (6, 7, 9, 12, and 15 mM). The concentration ranges for both cogerminants were selected to avoid data clusters in double reciprocal plots.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For taurocholate titrations, spores were exposed to various concentrations of taurocholate (8,10,14,20, and 30 mM) at specific constant glycine concentrations (8, 9, 10, 13, and 16 mM). For glycine titrations, spores were exposed to various concentrations of glycine (8,10,12,14, and 18 mM) at specific constant taurocholate concentrations (6, 7, 9, 12, and 15 mM). The concentration ranges for both cogerminants were selected to avoid data clusters in double reciprocal plots.…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative to genetic approaches, we have used kinetic methods and molecular probes to study Bacillus and Clostridium spore germination (1,3,14,30). These techniques allow proposing possible mechanisms for spore germination even when the identity of the germination receptors is not known (30).…”
mentioning
confidence: 99%
“…The nature of the spore germination signals has been studied widely in Bacilli and Clostridia (21,27,28,(44)(45)(46)(47)(48)(49)(50), but the triggers for P. larvae spore germination have not been identified. In order to cultivate P. larvae, specialized media have been produced (1,31,(51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
“…Structure activity relationship of nucleoside agonists and antagonists of B. cereus spore germination have shown that the GerI receptor is constrained to recognize a single germinant (inosine) and is inhibited in a predictable pattern by structurally related nucleosides. On the other hand, the GerQ receptor is more promiscuous toward nucleoside agonists and is inhibited by nucleosides containing hydrophobic groups at the 6-position (Dodatko et al, 2009a).…”
Section: Bacillus Cereus Ger Receptorsmentioning
confidence: 99%
“…Germination agonists and antagonists have been used to characterize the binding sites of B. cereus nucleoside receptors (Dodatko et al, 2009a). This approach could be extended to map germinant/Ger receptor interactions in other complexes.…”
Section: Future Directionsmentioning
confidence: 99%